1987
DOI: 10.1080/15287398709531009
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of diesel exhaust particles and oil shale particles dispersed in lecithin surfactant

Abstract: Diesel exhaust particulate material from exhaust pipe scrapings of two trucks, diluted automobile diesel exhaust particulate material collected on filters, and two oil shale ores were prepared for the Ames mutagenicity assay by dichloromethane (DCM) extraction, by dispersion into 0.85% saline, or by dispersion into dipalmitoyl lecithin (DPL) emulsion in saline. Salmonella typhimurium TA98 was used to detect frameshift mutagens in the samples. Samples of diesel soot gave positive mutagenic responses with both D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…When benzo[a]pyrene is particle-bound, clearance from hamster lungs is slower than that of pure benzo[a]pyrene aerosol, increasing the length of time the lungs are exposed and increasing the dose to the gastrointestinal tract as a result of mucocilliary clearance. Respirable benzo[a]pyrene-containing particulates such as diesel exhaust, when coated with the phospholipid component of a pulmonary surfactant, are genotoxic (Wallace et al, 1987). Dusts can increase the rates of pulmonary cell proliferation (Harris et al, 1971;Stenback and Rowland, 1979;Stenback et al, 1976), which in turn increases the cells' susceptibility to an initiation event in the presence of a carcinogen.…”
Section: Interactions With Other Substancesmentioning
confidence: 98%
“…When benzo[a]pyrene is particle-bound, clearance from hamster lungs is slower than that of pure benzo[a]pyrene aerosol, increasing the length of time the lungs are exposed and increasing the dose to the gastrointestinal tract as a result of mucocilliary clearance. Respirable benzo[a]pyrene-containing particulates such as diesel exhaust, when coated with the phospholipid component of a pulmonary surfactant, are genotoxic (Wallace et al, 1987). Dusts can increase the rates of pulmonary cell proliferation (Harris et al, 1971;Stenback and Rowland, 1979;Stenback et al, 1976), which in turn increases the cells' susceptibility to an initiation event in the presence of a carcinogen.…”
Section: Interactions With Other Substancesmentioning
confidence: 98%
“…Therefore, DPPC dispersed into physiological saline has been used as a simple model of lung surfactant and it was concluded that employing DPPC as dispersant for in vitro particle toxicity studies helps to mimic the real world exposure situation more closely and increases biological relevance [Wallace et al, 1987;.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous reports have dealt either directly or indirectly with the bioavailability of BaP associated with diesel particulate or other carbonaceous particulates. In in vitro studies, Wallace et al (1987) observed that dipalmitoylphosphatidylcholine (DPPC) extracts of diesel particulate were mutagenic in the Ames assay, indicating that mutagens were bioavailable. However, quantification of BaP or other mutagens was not performed.…”
Section: Discussionmentioning
confidence: 98%